Indicadores de desempenho como instrumentos de planejamento na gestão da saúde sendo objeto de estudos nos programas stricto sensu em administração no Brasil - Fernandes, José Edson Rodrigues (My University, 2022)
Health services do not always perform satisfactorily, especially when considering non-profit hospitals. This framework requires challenges for managers in the search for efficiency and effectiveness in the availability and treatment of information to improve hospital management, whether in the public or private sector. In this sense, the development and use of performance indicators or metrics constitute a fundamental element in the construction of efficient management. Within the context of this research, the objective was to identify and describe the contributions of research on health management planning instruments, as well as health performance indicators, carried out in Brazilian Stricto-Sensu Administration programs. In order to reach the objectives, descriptive bibliographic research was developed and in relation to the approach to the problem it is qualitative and consisted of the analysis of dissertations defended in the stricto sensu postgraduate programs in Administration, using the synthesis matrix to extract The informations. The results indicate the importance of using indicators in a differentiated multidimensional view, which conjecture the present health reality and allow the hospital manager, together with the health managers, a direction of care actions in the medium and long term. The indicators presented here are examples, among countless others, that one can try to standardize them in a set of metrics to be used by the Government, hospital manager and society. [resumo fornecido pelo autor]
Os serviços de saúde nem sempre apresentam desempenhos satisfatórios, principalmente quando observados os hospitais sem fins lucrativos. Esse quadro exige desafios aos gestores na busca de eficiência e eficácia na disponibilização e tratamento de informações para a melhoria da gestão hospitalar, seja no setor público ou privado. Neste sentido, o desenvolvimento e uso de indicadores ou métricas de desempenho constituem um elemento fundamental na construção de uma gestão eficiente. Dentro do contexto desta pesquisa, o objetivo foi identificar e descrever quais as contribuições das pesquisas sobre os instrumentos de planejamento da gestão da saúde, bem como dos indicadores de desempenho em saúde, realizadas nos programas de Stricto-Sensu em Administração brasileiros. Para o alcance dos objetivos, foi desenvolvida uma pesquisa bibliográfica de caráter descritivo e em relação à abordagem do problema é qualitativa e consistiu na análise das dissertações defendidas nos programas de pós-graduação stricto sensu em Administração, utilizando-se da matriz de síntese para extrair as informações. Os resultados indicam a importância da utilização de indicadores numa visão multidimensional diferenciada, que conjecturem a realidade de saúde presente e permita ao gestor hospitalar, juntamente com os gestores de saúde, um direcionamento das ações assistenciais a médio e longo prazo. Os indicadores aqui apresentados são exemplos, dentre outros existentes, que se pode tentar padronizá-los num conjunto de métricas a serem utilizadas pelo gestor hospitalar, governo e sociedade. [resumo fornecido pelo autor]
Keywords: Administração; Hospitais - Administração; Serviços de saúde - Administração; Desempenho - Indicadores; Management; Hospitals - Administration; Health services administration; Performance - Directories